EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH PADA LOMPAT JAUH GAYA MENGGANTUNG - Octavianus Cahyanto Adhie (Jurnal Educatio FKIP UNMA, 2020)
The learning improvement of physical education can be done through implementing learning approach which is suitable for 21st Century era. This research is a descriptive quantitative research which aims to describe the effectiveness of the hang style long jump learning using problem-based learning approach based on students’ learning outcomes and attitude in vocational high school context. The subject of the research were students of X ATR 1 and X TKRO 1 students of SMKN 1 Cangkringan. The data were obtained from the result of observation sheets, learning outcome tests, and questionnaire of students’ attitudes towards learning. The result showed that hang style long jump learning using problem-based learning approach was effective based on students’ learning outcomes and learning attitudes. The passing students reached 100% for X ATR 1 students and 83,87% for X TKRO 1 students. The students’ learning attitudes towards physical education subject in the category of minimum more than 80% high were 100% for X ATR 1 students and 87.095% for X TKRO 1 students.